A time-saving incremental cycle ergometer protocol to determine peak oxygen consumption. Issue 4 (December 1987) - Lawler, J; Powers, S K; Dodd, S
Abstract : Previously we have demonstrated that an accelerated arm ergometry testing protocol results in a higher peak oxygen consumption than continuous or discontinuous protocols reported in the literature (Brit. J. Sports Med. 20: 25-26, 1986). The purpose of this investigation was to determine if an accelerated protocol was superior to two commonly used protocols in cycle ergometry. Nine male subjects were tested on three different exercise protocols; a discontinuous test (DT), a continuous test (CT) and a new proposed "jump-max test" (JMT). The CT began at a work rate of 70 W with the power output (PO) being increased 35 W.min-1. The DT began at a work rate of 70 W; the work rate was increased by 35 W every 2 minutes with 2-minutes rest between stages. The JMT began with a 3-minute pretest to determine a PO which elicited a HR of 145 +/- 5 bpm. After a 2-minute rest, subjects began exercise at the predetermined work rate with the PO being increased 35 W.min-1. Testing sessions were terminated when subjects failed to maintain the desired PO. No significant difference (p greater than 0.05) existed in peak PO or peak oxygen consumption (VO2) between the three protocols. However, JMT protocol did result in a shorter time to exhaustion than the other protocols employed (P less than 0.05).